2008
DOI: 10.1002/srin.200806146
|View full text |Cite
|
Sign up to set email alerts
|

Some Strengthening Methods for Austenitic Stainless Steels

Abstract: Austenitic stainless steels possessing good corrosion resistance have recently found growing applications as a constructional material. In this instance, increasing strength properties, which are typically quite low, is of great interest. Due to the low stacking fault energy, strain hardening of alloyed austenite is efficient for increasing tensile strength without impairing ductility seriously. In addition, certain grades are unstable, so that cold working creates strain‐induced martensite that enhances stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(81 citation statements)
references
References 36 publications
2
59
0
1
Order By: Relevance
“…For a detailed microstructural analysis, a specific region beneath the fracture surface showing a bcc structure in the EBSD micrograph was prepared by a focusedion beam technique and then examined using TEM. The bright-field TEM image confirmed that α'-martensite was present mostly at the intersection area of deformation shear bands and had a Kurdjumov-Sachs (K-S) orientation relation with austenite [11][12][13]16] (Fig. 4(c)).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…For a detailed microstructural analysis, a specific region beneath the fracture surface showing a bcc structure in the EBSD micrograph was prepared by a focusedion beam technique and then examined using TEM. The bright-field TEM image confirmed that α'-martensite was present mostly at the intersection area of deformation shear bands and had a Kurdjumov-Sachs (K-S) orientation relation with austenite [11][12][13]16] (Fig. 4(c)).…”
Section: Resultssupporting
confidence: 63%
“…The chemical composition, nitrogen pressure, and M d30 temperature of the austenitic 18Cr-10Mn-N stainless steels fabricated in the present study are listed in Table 1. The M d30 temperature is widely used as a quantitative criterion to estimate austenite stability and is inversely related to austenite stability [11,12]. Thus, the 4Ni-3Mo-0.54N steel has higher austenite stability due to the addition of Ni and Mo, compared to the other steels.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the annealed state, their totally austenitic microstructure confers them an excellent ductility although limited yield stress. Cold deformation generates strain-induced martensite which, in addition to austenite strain hardening, results in a drastic improvement of yield stress [5] besides an excellent formability.…”
Section: Methodsmentioning
confidence: 99%
“…Anna KISKO, 1) * Juho TALONEN, 2) David Arthur PORTER 1) and Leo Pentti KARJALAINEN (Received on March 24, 2015; accepted on June 17, 2015) Highly refined grain size can be obtained in metastable austenitic stainless steels by martensitic reversion treatment, but the annealing must be controlled due to the high coarsening tendency of ultrafine grains. The effect of Nb microalloying on reversion and retardation of grain growth has been investigated in an austenitic 204Cu stainless steel containing Nb from 0 to 0.45 wt.%.…”
Section: Effect Of Nb Microalloying On Reversion and Grain Growth In mentioning
confidence: 99%